Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine which point is a solution to the given system of inequalities, we will evaluate each point against both inequalities:
[tex]\[ \begin{cases} -2x + 3y \geq 1 \\ -5x + 6y \leq 1 \end{cases} \][/tex]
Let's check each point one-by-one:
1. Point (6, 6):
For the first inequality, substitute [tex]\( x = 6 \)[/tex] and [tex]\( y = 6 \)[/tex]:
[tex]\[ -2(6) + 3(6) = -12 + 18 = 6 \quad (\text{which is } \geq 1) \][/tex]
This point satisfies the first inequality.
For the second inequality, substitute [tex]\( x = 6 \)[/tex] and [tex]\( y = 6 \)[/tex]:
[tex]\[ -5(6) + 6(6) = -30 + 36 = 6 \quad (\text{which is not } \leq 1) \][/tex]
This point does not satisfy the second inequality.
2. Point (7, 8):
For the first inequality, substitute [tex]\( x = 7 \)[/tex] and [tex]\( y = 8 \)[/tex]:
[tex]\[ -2(7) + 3(8) = -14 + 24 = 10 \quad (\text{which is } \geq 1) \][/tex]
This point satisfies the first inequality.
For the second inequality, substitute [tex]\( x = 7 \)[/tex] and [tex]\( y = 8 \)[/tex]:
[tex]\[ -5(7) + 6(8) = -35 + 48 = 13 \quad (\text{which is not } \leq 1) \][/tex]
This point does not satisfy the second inequality.
3. Point (8, 7):
For the first inequality, substitute [tex]\( x = 8 \)[/tex] and [tex]\( y = 7 \)[/tex]:
[tex]\[ -2(8) + 3(7) = -16 + 21 = 5 \quad (\text{which is } \geq 1) \][/tex]
This point satisfies the first inequality.
For the second inequality, substitute [tex]\( x = 8 \)[/tex] and [tex]\( y = 7 \)[/tex]:
[tex]\[ -5(8) + 6(7) = -40 + 42 = 2 \quad (\text{which is not } \leq 1) \][/tex]
This point does not satisfy the second inequality.
4. Point (9, 7):
For the first inequality, substitute [tex]\( x = 9 \)[/tex] and [tex]\( y = 7 \)[/tex]:
[tex]\[ -2(9) + 3(7) = -18 + 21 = 3 \quad (\text{which is } \geq 1) \][/tex]
This point satisfies the first inequality.
For the second inequality, substitute [tex]\( x = 9 \)[/tex] and [tex]\( y = 7 \)[/tex]:
[tex]\[ -5(9) + 6(7) = -45 + 42 = -3 \quad (\text{which is } \leq 1) \][/tex]
This point satisfies the second inequality.
The point [tex]\((9, 7)\)[/tex] satisfies both inequalities.
Therefore, the point [tex]\((9, 7)\)[/tex] is a solution to the system of inequalities.
[tex]\[ \begin{cases} -2x + 3y \geq 1 \\ -5x + 6y \leq 1 \end{cases} \][/tex]
Let's check each point one-by-one:
1. Point (6, 6):
For the first inequality, substitute [tex]\( x = 6 \)[/tex] and [tex]\( y = 6 \)[/tex]:
[tex]\[ -2(6) + 3(6) = -12 + 18 = 6 \quad (\text{which is } \geq 1) \][/tex]
This point satisfies the first inequality.
For the second inequality, substitute [tex]\( x = 6 \)[/tex] and [tex]\( y = 6 \)[/tex]:
[tex]\[ -5(6) + 6(6) = -30 + 36 = 6 \quad (\text{which is not } \leq 1) \][/tex]
This point does not satisfy the second inequality.
2. Point (7, 8):
For the first inequality, substitute [tex]\( x = 7 \)[/tex] and [tex]\( y = 8 \)[/tex]:
[tex]\[ -2(7) + 3(8) = -14 + 24 = 10 \quad (\text{which is } \geq 1) \][/tex]
This point satisfies the first inequality.
For the second inequality, substitute [tex]\( x = 7 \)[/tex] and [tex]\( y = 8 \)[/tex]:
[tex]\[ -5(7) + 6(8) = -35 + 48 = 13 \quad (\text{which is not } \leq 1) \][/tex]
This point does not satisfy the second inequality.
3. Point (8, 7):
For the first inequality, substitute [tex]\( x = 8 \)[/tex] and [tex]\( y = 7 \)[/tex]:
[tex]\[ -2(8) + 3(7) = -16 + 21 = 5 \quad (\text{which is } \geq 1) \][/tex]
This point satisfies the first inequality.
For the second inequality, substitute [tex]\( x = 8 \)[/tex] and [tex]\( y = 7 \)[/tex]:
[tex]\[ -5(8) + 6(7) = -40 + 42 = 2 \quad (\text{which is not } \leq 1) \][/tex]
This point does not satisfy the second inequality.
4. Point (9, 7):
For the first inequality, substitute [tex]\( x = 9 \)[/tex] and [tex]\( y = 7 \)[/tex]:
[tex]\[ -2(9) + 3(7) = -18 + 21 = 3 \quad (\text{which is } \geq 1) \][/tex]
This point satisfies the first inequality.
For the second inequality, substitute [tex]\( x = 9 \)[/tex] and [tex]\( y = 7 \)[/tex]:
[tex]\[ -5(9) + 6(7) = -45 + 42 = -3 \quad (\text{which is } \leq 1) \][/tex]
This point satisfies the second inequality.
The point [tex]\((9, 7)\)[/tex] satisfies both inequalities.
Therefore, the point [tex]\((9, 7)\)[/tex] is a solution to the system of inequalities.
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.